Effects of Yoga-teaching and Practices on Learning and Studying Behaviour of Management Students: An Experimental Study - Aryal, Lal Prasad (The Batuk, 2022)
Learning and studying are fairly cognitive and psychological activities that need sound mental health including inner-peace, calmness, easiness, positivity, curiosity, interest, and self-motivation. The increased interest in yoga-teaching and practices (YTP) in recent decades is primarily due to the expectancy that it can calm the mind and increase the overall health and well-being of the students. Yoga provides training of mind and body to bring emotional and mental balance as well as leads to alignment and harmony. This article discusses yoga (particularly, Asanas, Pranayamas, and Dhyanas) as a potential tool for the management students to deal with mental health that is essentially important for effective learning and studying behavior and to regulate themselves. For this experimental study, 60 students are taken as a sample who were failed in their mid-term examination and they are further classified as self-control group and experimental group with 30 students in each group. This study finding suggests that YTP is an effective tool to solve mental health issues and finally it contributes to effective learning and studying habits of management students.It is also found that YTP contributes to mental health promotion of students for which they need to improvement their attention, self-esteem, empowerment, and self-regulation.